Gene Expression of IGF1, IGF1R, and IGFBP3 in Epiretinal Membranes of Patients with Proliferative Diabetic Retinopathy: Preliminary Study - Dorota Romaniuk; Malgorzata W. Kimsa; Barbara Strzalka-Mrozik; Magdalena C. Kimsa; Adam Kabiesz; Wanda Romaniuk; Urszula Mazurek (Mediators of Inflammation)
The molecular mechanism formation of secondary epiretinal membranes (ERMs) after proliferative diabetic retinopathy (PDR) or primary idiopathic ERMs is still poorly understood. Therefore, the present study focused on the assessment of IGF1, IGF1R, and IGFBP3 mRNA levels in ERMs and PBMCs from patients with PDR. The examined group comprised 6 patients with secondary ERMs after PDR and the control group consisted of 11 patients with idiopathic ERMs. Quantification of IGF1, IGF1R, and IGFBP3 mRNAs was performed by real-time QRT-PCR technique. In ERMs, IGF1 and IGF1R mRNA levels were significantly higher in patients with diabetes compared to control subjects. In PBMCs, there were no statistically significant differences of IGF1, IGF1R, and IGFBP3 expression between diabetic and nondiabetic patients. In conclusion, our study indicated IGF1 and IGF1R differential expression in ERMs, but not in PBMCs, of diabetic and nondiabetic patients, suggesting that these factors can be involved in the pathogenesis or progression of proliferative vitreoretinal disorders. This trial is registered with NCT00841334.